Analisis Tingkat Kepuasan Pasien Rawat Inap Terhadap Kualitas Mutu Pelayanan di Rumah Sakit PKU ‘Aisyiyah Kendal - Sifa’ul Kumairoh; Atika Nurani Ambarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Achieving a level of satisfaction with the quality of services provided to patients, both the quality of health services and the health service system, will be the main choice for patients who come to the hospital. This study aims to analyze the level of satisfaction of inpatients with the quality of service at PKU 'Aisyiyah Kendal Hospital. This research uses the Service Quality (ServQual) and Importance Performance Analysis (IPA) methods. Data was obtained from distributing questionnaires to 99 inpatients using purposive sampling techniques based on inclusion and exclusion criteria. The overall average result of the level of reality and the level of expectations is that the conformity level is 99.4%, so it cannot be stated that it meets patient satisfaction or it can be stated that the quality of service provided by PKU 'Aisyiyah Kendal Hospital is not yet satisfactory because the conformity level is still below 100%. This indicates the need to improve services to meet patient expectations so as to achieve inpatient satisfaction. The priority attribute of PKU 'Aisyiyah Kendal Hospital is that the inpatient room is neatly arranged and clean, including the bathroom (quadrant I). It is hoped that the management of PKU 'Aisyiyah Kendal Hospital will be serious in dealing with these attributes or factors and make improvements because many patients feel dissatisfied.